2016
DOI: 10.1016/j.scitotenv.2016.01.111
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mobility of arsenic and heavy metals in soils polluted by the destruction of arsenic-containing shells from the Great War

Abstract: Destruction of chemical munitions from World War I has caused extensive local top soil contamination by arsenic and heavy metals. The biogeochemical behavior of toxic elements is poorly documented in this type of environment. Four soils were sampled presenting different levels of contamination. The range of As concentrations in the samples was 1937-72,820mg/kg. Concentrations of Zn, Cu and Pb reached 90,190mg/kg, 9113mg/kg and 5777mg/kg, respectively. The high clay content of the subsoil and large amounts of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 34 publications
(20 reference statements)
5
37
0
1
Order By: Relevance
“…Despite the severe contamination, microorganism activity, contributing to carbon (C) and As biogeochemistry, was detected in this technosol (Thouin et al, 2016). However, the structure of the microbial community on this particular site has not yet been determined.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Despite the severe contamination, microorganism activity, contributing to carbon (C) and As biogeochemistry, was detected in this technosol (Thouin et al, 2016). However, the structure of the microbial community on this particular site has not yet been determined.…”
Section: Introductionmentioning
confidence: 88%
“…In previous work, we showed that intrinsic organic matter (OM), mainly composed of charcoal from the contaminated material, is very high (≈ 25 %) (Thouin et al, 2016). This OM is characterized by high C/N (≈ 35) and low hydrogen index/oxygen index (HI/OI ≈ 0.1) and is therefore recalcitrant in nature (Thouin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an inverse correlation between pH (slight to moderate alkaline) and metals (e.g., pH-Al = − 0.19 and pH-Mn = −0.43). Several studies have found a negative correlation between pH and metal mobility; elements are more mobile in acid conditions (Wang et al 2006;Fanrong et al 2011;Thouin et al 2016) and their increasing absorption in plants and humans threatens their health (Saiful Islam et al 2015;Gu et al 2016). Organic carbon does not show any strong or appreciable correlation with the considered variables.…”
Section: Lipid Peroxidation Quantificationmentioning
confidence: 96%